Dispersibility and Storage Stability Optimization of High Dose Isoniazid Dry Powder Inhalation Formulations with L-Leucine or Trileucine - Imco Sibum; Paul Hagedoorn; Markus P. G. Kluitman; Martijn Kloezen; Henderik W. Frijlink; Floris Grasmeijer (MDPI AG, 2019)
Tuberculosis is the leading cause of death from a single infectious pathogen worldwide. Lately, the targeted delivery of antibiotics to the lungs via inhalation has received increasing interest. In a previous article, we reported on the development of a spray-dried dry powder isoniazid formulation containing an L-leucine coating. It dispersed well but had poor physical stability. In this study, we aimed to improve the stability by improving the leucine coating. To this end, we optimized the spray-drying conditions, the excipient content, and the excipient itself. Using L-leucine, the tested excipient contents (up to 5%) did not result in a stable powder. Contrary to L-leucine, the stability attained with trileucine was satisfactory. Even when exposed to 75% relative humidity, the formulation was stable for at least three months. The optimal formulation contained 3% trileucine w/w. This formulation resulted in a maximum fine particle dose of 58.00 ± 2.56 mg when a nominal dose of 80 mg was dispersed from the Cyclops® dry powder inhaler. The improved moisture protection and dispersibility obtained with trileucine are explained by its amorphous nature and a higher surface enrichment during drying. Dispersion efficiency of the device decreases at higher nominal doses.